Perbandingan Uji Diagnostik Mesothelin Serum dengan CA-125 pada Kanker Ovarium Tipe Epitel - USHAN, ERI PERDANA; ASKANDAR T, BRAHMANA; BUDIONO, BUDIONO (Indonesian Journal of Cancer, 2015)
This study was conducted to determine and compare the sensitivity, specificity, PPA and NPV of Mesothelin tumor marker, CA-125, combination of Mesothelin and CA-125 as a tumor marker in patients with epithelial ovarian carcinoma. This is a cross sectional diagnostic test on 30 subjects with malignant dan 30 sunjects with benign ovarian tumors that meet the inclusion and exclusion of research criteria in Department of Obstetrics and Gynecology, Medical Faculty Airlangga University/Dr. Soetomo, Surabaya. Blood sample were taken prior to surgery to examine tumor markers (Mesothelin and CA-125) and ultrasound to evaluate tumor mass, and then histopathology of surgery specimen. Statistical data calculated using SPSS. There is a significant increase of Mesothelin serum level and can be used as a tumor marker (alone or in combination with other methods as a triage tool, consider the use of new cut-off value of 1.75 nmol/L). Sensitivity, specificity, PPV, NPV of CA125 is 70%, 33.3%, 51.2% and 52.6%. Sensitivity, specificity, PPV, NPV of Mesothelin-1 is 50%, 80%, 71.4% and 61.5%. Sensitivity, specificity, PPV, NPV of Mesothelin-2 is 36.7%, 93.4%, 84.6% and 59.6%. Sensitivity, specificit , PPV, NPV combination of CA-125 + Mesothelin-1 is 33.3%, 86.7%, 71.4%, 56.5% and 60%. Sensitivity, specificity, PPV, NPV combination of CA-125 + Mesothelin-2 is 23.3%, 93.3%, 77.8%, and 54.9%. Sensitivity, specificity, PPV, NPV of RMI is 83.3%, 36.7%, 56.8%, and 68.8%. CA-125 (as a single tumor marker) has the highest sensitivity and proved as a simple and effective method for the early detection at general population. Mesothelin-2 (either as a single tumor marker or in combination) is more appropriate for the diagnosis tools (triage, determining the risk of malignant from benign ovarian masses) are better than the current and can be considered to replace CA-125.Keywords: tumor marker, CA-125, Mesothelin, combine tumor marker.ABSTRAKPenelitian ini bertujuan mengetahui dan membandingkan sensitivitas, spesifisitas, PPV, dan NPV antara penanda tumor Mesothelin, CA-125, dan kombinasi Mesothelin dan CA-125 sebagai penanda tumor pada penderita keganasan ovarium tipe epitel. Penelitian ini merupakan uji diagnostik cross sectional terhadap 30 pasien tumor jinak dan 30 pasien tumor ganas tumor ovarium yang memenuhi kriteria inklusi dan kriteria eksklusi di Bagian Obstetri dan Ginekologi FK-Unair/RSU Dr. Soetomo, Surabaya. Dilakukan pengambilan serum darah untuk memeriksa tumor marker (Mesothelin dan CA-125) dan pemeriksaan ultrasonografi sebelum dilakukan tindakan pembedahan. Kemudian dilakukan pemeriksaan patologi anatomi spesimen operasi. Penghitungan data statistik menggunakan SPSS. Hasil penelitian menunjukkan terdapat peningkatan kadar serum Mesothelin yang dapat digunakan sebagai pemeriksaan penanda tumor tunggal atau kombinasi sebagai alat triase dengan mempertimbangkan penggunaan nilai cut-off 1,75 nmol/L. Sensitivitas, spesifisitas, PPV, dan NPV CA125 adalah 70%; 33,3%; 51,2%; dan 52,6%. Sensitivitas, spesifisitas, PPV, dan NPV Mesothelin-1 adalah 50%; 80%; 71,4%; dan 61,5%. Sensitivitas, spesifisitas, PPV, dan NPV Mesothelin-2 adalah 36,7%; 93,4%; 84,6%; dan 59,6%. Sensitivitas, spesifisitas, PPV, dan NPV kombinasi CA-125 + Mesothelin-1 adalah 33,3%; 86,7%; 71,4%; 56,5%; dan 60%. Sensitivitas, spesifisitas, PPV, dan NPV kombinasi CA-125 + Mesothelin-2 adalah 23,3%; 93,3%; 77,8%; dan 54,9%. CA-125 (sebagai penanda tumor tunggal) memiliki sensitivitas tertinggi sehingga merupakan metode sederhana dan efektif untuk deteksi dini pada populasi. Mesothelin-2 (baik sebagai penanda tumor tunggal maupun dalam kombinasi) lebih tepat untuk proses penegakan diagnosis (triase, penentuan risiko massa ovarium ganas dari jinak) yang lebih baik dan dapat menggantikan CA-125.Kata Kunci: penanda tumor, CA-125, Mesothelin, kombinasi CA-125 dan Mesothelin